CCAFS supports implementation of the Regional Strategy for Disaster Risk Management in the Agriculture Sector and Food and Nutrition Security in Latin-America and the Caribbean - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CCAFS' Local Technical Agroclimatic Committees (LTAC) approach was selected as a tool to implement the Regional Strategy for Disaster Risk-Management in the Agriculture-Sector and Food and Nutrition Security in Latin America. Two major successes have been achieved, Chile adds to the group of Latin American countries that have adopted the LTAC approach (5 total), and Peru, Bolivia, Paraguay, and Ecuador are designing their plans to implement the approach according to their context-specific needs and capacities supported by FAO-CCAFS collaborative work.